PENDEKATAN PROTIBING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MATERI METABOLISME MELALUI PENERAPAN TEKNIK MUSIKALISASI - Sasmito, Agung Probo (BIOMA, 2015)
The background of this research was lowed activity and studentâslearning outcome of class XII IPA 1. The problem was how theactivitiy and learning outcomes could be improved. The purpose wasto improved activity and learning outcomes from metabolism topic inXII IPA 1 SMAN 1 Lasem. The research was used PROTIBING(Creativity Guided Process) through musical technique application.Classical learnerâs average percentage in first cycle was 71.49%,increased to 76.97% in the second cycle, itâs achieved the specifiedperformance indicators, 70%. The result for learning outcome, 72.1%in first cycle and increased in the second cycle, 83.2%. The first cycleof performance didnât reached 75, but the second cycle increased andexceeded the performance indicators. The final conclusion forPROTIBING through musical technique application increased theactivity and learning outcomes of students in XII IPA 1 of SMAN 1Lasem.Keywords: Activity Learning, Learning Outcomes, PROTIBING(Guided Creative Process), Technique Musical.